Two new Gordionus species (Nematomorpha: Gordiida) from the southern Rocky Mountains (USA) - Begay, Alyssa C.; Schmidt-Rhaesa, Andreas; Bolek, Matthew G.; Hanelt, Ben (Zootaxa, 2012)
The phylum Nematomorpha contains approximately 350 species in 19 extant genera. The genus Gordionus contains 56species, four of which occur in the contiguous United States of America. Here we describe two new Gordionus speciesfrom the southern Rocky Mountains. Worms were collected at three sites in the Santa Fe National Forest in northern NewMexico in the southernmost tip of the Rocky Mountains. Sites consisted of first order streams above 3120m in aspen/pinewoodland. Gordionus lokaaus n. sp. has flat, polygonal or roundish, areoles covering all parts of the body. The male cloa-cal opening is surrounded by broad bristles with stout apexes forming a unique tube-like opening. Adhesive warts aresmall and postcloacal spines are thin and triangular-shaped. Gordionus bilaus n. sp. also has flat polygonal or roundshaped areoles, but has indistinct interareolar furrows making neighboring areoles appear fused. The male cloacal openingis surrounded by stout, finger-like bristles in 2‒3 rows. Adhesive warts are larger and postcloacal spines are broad andmound-shaped. These species double the number known from the state of New Mexico and are the first gordiids described from the southern part of the Rocky Mountains.